2013
DOI: 10.1177/0734242x13477718
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives for solid waste management in Isfahan, Iran: a case study

Abstract: This articles presents the status of municipal solid waste (MSW) management practices in the city of Isfahan, Iran. It provides an overview of the generation, collection, separation, recycling and disposal of MSW. Field studies were carried out from 2009 to 2010. According to this study, the city generates about 399,000 metric tons of MSW per year, of which 72.5% is organic matter. In Isfahan more than 90% of the MSW is collected by official municipal forces and the other 10% is collected by informal collector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…According to Abduli et al (2013), it is essential to comprehend the quantity and type of USW generated in order to plan and develop a suitable management policy for these materials in a specific location. Moreover, the lack of knowledge, mainly about MSW quantity and its characteristics, can make some stages not viable, such as treatment and the final disposal (Costa et al, 2012).…”
Section: Generation and Composition Of Uswmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Abduli et al (2013), it is essential to comprehend the quantity and type of USW generated in order to plan and develop a suitable management policy for these materials in a specific location. Moreover, the lack of knowledge, mainly about MSW quantity and its characteristics, can make some stages not viable, such as treatment and the final disposal (Costa et al, 2012).…”
Section: Generation and Composition Of Uswmentioning
confidence: 99%
“…Inadequate management of USW in terms of treatment results in economic losses and poses a threat to public health and natural resources (Abduli et al, 2013). Zhang et al (2010) affirm that any activity for USW treatment not only diminishes the total amount of waste generated but also the costs of disposal.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improper disposal and management of these waste materials could be associated with many serious environmental and health challenges . Land and water pollution due to waste disposals have shown numerous disadvantages, including the reduction of viable arable farmland for domestic and commercial agriculture and the scarcity of fresh water for human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing quality and quantity of waste in Isfahan, Iran showed that the rate of waste generation is 1090 t, out of which 65% were organic materials, 25% recycled materials and 5-10% other materials. His cost-benefit analysis revealed that waste incineration could be recommended as a suitable approach for improving waste management through energy recovery (Abdoli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%